A cooperation guarantee mechanism based on altruistic punishment for nodes in distributed environments. (2017) - Liu, Jiaqi; Wang, Guojun; Chen, Zhigang; Liu, Hui
Aiming at non-cooperation behaviours in highly distributed environments such as P2P systems, researchers have presented many algorithms and mechanisms based on traditional economic theories. The hypothesis of rational man is the basic assumption in traditional economic theories. The hypothesis means that any man is a rational man who is selfish and desires to maximise his needs or desires. However, researches on behaviour economics have proved by many demonstrations that the assumption of rational man is defective. Research achievements in demotics and other fields find that humans have a predisposition to punish those who violate group-beneficial norms, even when this imposes a fitness cost on the punisher. Based on the altruistic punishment, we present a whole new mechanism considering both rational nodes and irrational nodes in distributed environments reference from rational man and irrational man in social area without central controller. A mechanism based on altruistic punishment is proposed to improve the cooperation degree. Theory analysis and simulation results prove the ration and validity of this paper.